AKUNTABILITAS PENGELOLAAN DANA DESA PADA MASA PANDEMI COVID-19 MENURUT PERSPEKTIF SHARIA ENTERPRISE THEORY - HAERIANTI HERIANTI (AL-IQTISHAD: Jurnal Ekonomi, 2022)
This study discusses the Accountability of Village Fund Management during the Covid-19 Pandemic in Mattanete Bua, Bone Regency in 2020. The purpose of this study is to describe the Form and Results of Village Fund Management Accountability during the Pandemic Period and its perspective according to Sharia Enterprise Theory. The research method used is qualitative with a sociological and phenomenological approach. The results of the study show 1) the form of accountability for managing funds during the Covid-19 pandemic in Mattanete Bua is an accountability report that is made in an orderly, complete and in accordance with applicable regulations, so that it can be said to be accountable. 2) Implementation of Village Fund Management Accountability according to the Sharia Enterprise Theory perspective is known as the trilogy of accountability relationship dimensions, namely accountability to God, humans and nature. The results show that the advantages of accountability are still human-centred.